Au(iii)-aryl intermediates in oxidant-free C–N and C–O cross-coupling catalysis. Issue 2 (3rd October 2016) - Serra, Jordi; Parella, Teodor; Ribas, Xavi
Abstract : Au(iii )-aryl species have been crystallographically isolated as reactive intermediates in oxidant-free C–O and C–N cross coupling processes, using aromatic and aliphatic alcohols and amines, as well as water and amides, as nucleophiles. Abstract : Au(iii )-aryl species have been unequivocally identified as reactive intermediates in oxidant-free C–O and C–N cross coupling catalysis. The crystal structures of cyclometalated neutral and cationic Au(iii ) species are described and their key role in 2 electron-redox Au(i )/Au(iii ) catalysis in C–O and C–N cross couplings is shown. Nucleophiles compatible with Au-catalyzed cross couplings include aromatic and aliphatic alcohols and amines, as well as water and amides.